SIMPLE MINI AMPLIFIER - Hendro Yuhanto; Ir Aqwam Rosadi K. (Jurnal Sistem Komputer, 1999)
simple mini amplifier is a device that has the function to strengthen the weak voice becomes stronger. Experiment has constraints because there is an electronic component that is not easily available and already there is no market.